Mengeksplorasi Strategi Variasi Produk Untuk Meningkatkan Loyalitas Pelanggan: Studi Kualitatif di Palapa Toserba Wadung Asri - Rohmawati Rohmawati; Siti Aisyah; Eli Masnawati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Customer loyalty is a key aspect for the success and desirability of a retail business. Product variations can be an effective approach to increasing customer loyalty. However, in-depth understanding of various product strategies that can increase customer loyalty is still limited. The aim of this research is to explore and understand the variations in product strategies that can be implemented by Palapa Toserba to increase customer loyalty. This research uses a qualitative approach, data is collected through interviews with customers and observation. The results of this research can increase customer loyalty. This research provides valuable insight for Palapa Toserba Wadung Asri and other retail companies in implementing effective product variety strategies to increase customer loyalty